THE INFLUENCE OF DIGITAL MARKETING AND ELECTRONIC WORD OF MOUTH (E-WOM) ON PURCHASE INTENTION - Aida Fitri; Ammar Fuad (GREET, 2026)
This study aims to examine and analyze the influence of digital marketing and electronic word of mouth (e-WOM) on purchase intention. This research employs a quantitative approach. The total sample in this study was 100 respondents. The sample was determined using the Slovin formula and selected using an accidental sampling technique. Data were collected through a structured questionnaire and analyzed using multiple linear regression analysis with a confidence level of 95% (α = 0.05). The results of this study indicate that digital marketing has a significant effect on purchase intention. Electronic word of mouth (e-WOM) also has a significant effect on purchase intention. Simultaneously, digital marketing and e-WOM have a significant influence on purchase intention. These findings suggest that effective digital marketing strategies and positive online reviews can increase consumers’ intention to purchase.